Evaluation method of shale reservoir fracability based on double sweet spots - SHI Can; LIN Botao; XIE Bobo; PAN Yuting; ZHANG Jiahao (Shenzhen Daxue xuebao. Ligong ban)
The sweet spot and fracability evaluation of shale reservoirs are crucial benchmarks for shale reservoir exploration. Currently, the the similarity in the parameter selection and mathematical approache for sweet spot and fracability evaluation gives rise to several issues, including conceptual confusion, ambiguous interrelationships, and redundant evaluations. There is an urgent need to clarify the connection between sweet spots and fracability while establishing a standardized evaluation method. This study systematically investigates the commonly-used sweet spots and fracability evaluation methods and clarifies the relationship among geological sweetness index (GSI), engineering sweetness index (ESI), and fracability based on conceptual understanding and evaluation methods. Building upon this groundwork, a comprehensive sweet spot-based fracability evaluation method is proposed. This method leverages on-site geology and engineering parameters to calculate GSI and ESI, and then constructs the reservoir fracability index (FI) and regional compressibility evaluation plate, which facilitates a rapid and quantitative assessment of the fracability of single wells. By selecting the geological and engineering parameters of 10 shale gas wells in the Weiyuan block of the Sichuan Basin, GSI, ESI, and FI are calculated using the established method. It is observed that FI has a positive correlation with the actual testing well gas production with an equal proportion for different wells. This method can provide effective scientific guidance for optimizing the well trajectory, increasing the drilling encounter rate with high-quality reservoirs, and optimizing the construction plan of reservoir fracturing.